Stabilizing ion and radical ion pair states in a paramagnetic endohedral metallofullerene/π-extended tetrathiafulvalene conjugate - Takano, Yuta; Obuchi, Shota; Mizorogi, Naomi; Garcia, Raul; Angeles Herranz, M.; Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2012)
Electron donor-acceptor conjugates of paramagnetic endohedral metallofullerenes and π-extended tetrathiafulvalene (exTTF) were synthesized, characterized, and probed with respect to intramolecular electron transfer involving paramagnetic fullerenes. UV-vis-NIR absorption spectroscopy complemented by electrochemical measurements attested to weak electronic interactions between the electron donor, exTTF, and the electron acceptor, La@C , in the ground state. In the excited state, photoexcitation powers a fast intramolecular electron transfer to yield an ion and radical ion pair state consisting of one-electron-reduced La@C and of one-electron-oxidized exTTF. © 2012 American Chemical Society.